Pengembangan kualitas dan keunggulan kepemimpinan dalam organisasi: peran moderasi nilai-nilai kearifan lokal - Pieter Sahertian; Umiati Jawas; David Sukardi Kodrat (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2022)
Various research results show that everything that is expected of a leader, what a leader can and cannot do, as well as the status and influence exerted by a leader is the result of the culture in the country where the leader performs his function. Therefore, to be an effective leader one must have the capacity that is obtained through developing leadership skills in the social context in which he is located. This study aims to analyze the effect of developing leadership skills and local wisdom values in forming leadership excellence in Indonesia. The research method used quantitative. The research sample was the leaders of Javanese, Sundanese, Betawi, Minang, Bugis, Batak, Madurese, Balinese, Banjar, Menado, Mataram, Flores and Papuan ethnic groups with a total of 710 respondents. A cluster and purposive sampling technique were used because the leaders as the unit of analysis were grouped into clusters based on ethnicity and region and then the leaders who were selected based on the objectives of the study. SEM analysis was used to data analysis and hipothesis testing. This study shows that the development of leadership abilities and local wisdom values can significantly increase the dimensions of leadership excellence. Besides, the values of local wisdom are able to moderate the influence of developing leadership abilities on leadership excellence.